BIOMONITORING PENCEMARAN PERAIRAN MENGGUNAKAN ALGA HIJAU-BIRU (Cyanobacteria) SEBAGAI BIOINDIKATOR - Nur aini; Fathul Mu’in; Slamet Mardiyanto Rahayu (LPPM, Akademi Administrasi Rumah Sakit Mataram, 2025)
Biomonitoring of water pollution is an important method for assessing environmental quality sustainably. Increased human activities, such as industrial, agricultural, and domestic activities, have led to the introduction of various pollutants into water bodies, disrupting the balance of aquatic ecosystems. One effective approach to biomonitoring is the use of living organisms as bioindicators, including blue-green algae or cyanobacteria. This study aims to analyze the role of cyanobacteria as bioindicators of water pollution based on various scientific literature. The method used is a literature review, analyzing research results from national and international journals descriptively. The results indicate that cyanobacteria are highly sensitive to changes in water quality, particularly increases in nutrient content such as nitrogen and phosphorus, which can trigger eutrophication and blooms. Furthermore, some cyanobacteria species are capable of producing toxic compounds (cyanotoxins) that are harmful to humans and other organisms, making their presence an indicator of environmental health risks. Thus, cyanobacteria can be used as effective, practical, and economical bioindicators in biomonitoring activities to assess the level of pollution and the ecological condition of water bodies.